Resistance index of the umbilical arteries and fetal brain in normal pregnancies average 20 to 40 weeks. - Huamán, Moisés (2015)
OBJECTIVE: To determine the resistance index (RI) of umbilical artery and fetal middle cerebral artery in normal patients enrolled in the second half of pregnancy. DESIGN: Prospective study of pregnant women without complications from 20 weeks to term. MATERIALS AND METHODS: 125 patients with no risk factors were selected. The resistance index was evaluated in the umbilical artery and middle cerebral artery using equipment Logiq 500 MD / MR 3 GE. RESULTS: IR umbilical artery at 20 weeks is about 0,750; then decreases steadily, faster between 26 and 34 weeks and at the end of gestation, it is less than 0,600. The IR fetal middle cerebral artery of a mean value close to 0,900 at 20 weeks, showing a rapid decline up to 24 weeks and then maintain a slow and gradual decline until the end, with around 0,700. CONCLUSION: During the second half of pregnancy flow resistance measured by IR fetal middle cerebral artery, is greater than the umbilical artery, usually with a ratio greater than one.